The effectiveness of implementing student physical perfectness techniques for creative thinking development - Tulegen Botagariyev; Aibek Gabdullin; Aiymgul Akhmetova; Zhaxybek Zhunusbekov; Nurbol Saitbekov (International Journal of Evaluation and Research in Education (IJERE), 2023)
Supporting students’ physical development and creativity under the influence of modern globalization is one of the key tasks for today’s science community. The present study aims to develop an individual program of physical and creative development in first- and second-year female students, taking account of their educational and anthropometric characteristics. Students’ level of creative thinking was assessed according to William’s methodology, and a physical education program for experimental group respondents was developed to link the two factors. Consequently, the program’s implementation demonstrated significant changes in the respondents’ creative thinking towards a positive gradation. The number of respondents with low creative thinking scores in the primary follow-up survey increased to an average of 120 students. At the same time, the Chi-square analysis to compare the experimental and control sample in detail indicates that experimental and control sample designs are consistent (χ2=122.77). This study may be used in more in-depth research on the interrelationships between youth’s physical and creative development. Besides, it can also serve as a prototype for implementing associated integrated student development programs at the university.